Analysis of Decisions of The General Meeting of Shareholders That Have a Balanced Percentage of Share Ownership - Zaky Zhafran King Mada (Veteran Law Review, 2023)
This Legal Research is entitled Juridical Analysis of the decisions of the General Meeting Of Shareholders (GMS) that have a balanced percentage of ownership in a limited liability company. If there is a Limited Liability Company in which there are only 2 (two) shareholders who have a balanced percentage of ownership so that there is a problem, namely that one of the shareholders does not attend the GMS or one of the shareholders does not agree on a GMS decision. The provisions regarding the quorum of the GMS and the decisions of the GMS have been determined with certainty, but in reality problems regarding this are still encountered. This research based on by 2 (two) problem formulations, the first is how to regulate shareholders who have a balanced percentage of ownership in the legislation, then the second is how the legal steps should be taken by shareholders. The First results of this study are if the two shareholders still have different interests then the Company is unlikely to continue. Because the two shareholders are decision makers, and if the deadlock continues then this will have an impact on the Company. In this case, the district court may dissolve the Company on the grounds that it is impossible for the Company to continue. And the Second, is a legal step that can be taken by one of the shareholders is to apply for an application to the district court, namely by requesting a quorum and the decision of the GMS.